The Effect of Incremental Aerobic Exercise in Dusty Air on Pulmonary Function Indicators of Non-Athletic Overweight Men - Ameneh Balavi; Hojaat Allah Nik bakht; Mandana Gholami; khosro ebrahim (Islamic Azad University, 2016)
Introduction: Dust has become one of the serious problems of people, and (more) especially in the cities of western and southwestern Iran. Despite the importance of the issue of dust, little has been done on this phenomenon, and there are many questions about many aspects of this phenomenon. This study sought to investigate the effect of aerobic exercise in dust -filled air and compare it with clean air on non-athletic overweight male using pulmonary function indicators. Methods: Of the eligible candidates, 30 persons were selected in a targeted and accessible manner. The subjects were given two separate days in the clean and dusty air at the physiology lab of the Islamic Azad University of Sousangerd to perform a daily treadmill incremental aerobic exercise session. A spirometry test was used to determine the pulmonary function indicators before and after an incremental exercise test session in both days of clean air and high dust (with similar humidity and temperature). For statistical analysis of data Kolmogorov-Smirnov test and paired sample t test (p≤0.05) were used. Results: Paired sample t test for changes in both airs indicated that there was significant difference in changes of FEV1 (p=0.004) and MVV (p=0.004) after incremental aerobic exercise between clean and dusty airs, nevertheless there were no significant difference in changes of FVC (p=0.27), FEV1/FVC (p=0.50) and VC (p=0.16) after incremental aerobic exercise between clean and dusty airs. Conclusion: One session of incremental aerobic exercise in dusty air is associated with decreasing pulmonary function indicators and decreasing pulmonary function capacity.